Heat-Activated Persulfate Oxidation of Chlorinated Solvents in Sandy Soil - Jialu Liu; Xijun Gong; Shijun Song; Fengjun Zhang; Cong Lu (Journal of Spectroscopy)
Heat-activated persulfate oxidative treatment of chlorinated organic solvents containing chlorinated ethenes and ethanes in soil was investigated with different persulfate dosages (20 g/L, 40 g/L, and 60 g/L) and different temperatures (30°C, 40°C, and 50°C). Chlorinated organic solvents removal was increased as persulfate concentration increase. The persulfate dosage of 20 g/L with the highest OE (oxidant efficiency) value was economically suitable for chlorinated organic solvents removal. The increasing temperature contributed to the increasing depletion of chlorinated organic solvents. Chlorinated ethenes were more easily removed than chlorinated ethanes. Moreover, the persulfate depletion followed the pseudo-first-order reaction kinetics (kps=0.0292 [PS]0+0.0008, R2=0.9771). Heat-activated persulfate appeared to be an effective oxidant for treatment of chlorinated hydrocarbons.